Comparison of a novel tablet formulation of tacrolimus and conventional capsule formulation in de novo kidney transplant recipients: a systematic review and meta-analysis - Liu, Zhenyu; Yin, Kexin; Liu, Huiqian; Wang, Ning; Yao, Junjie; Zhou, Jiangtao; Tang, Yongxi; Yin, Zhikang (Frontiers in Pharmacology, 2023)
Background: To compare the pharmacokinetic (PK) profiles and other outcomes reported in observational studies in de novo kidney transplant recipients (KTRs) receiving novel once-daily extended-release tablet tacrolimus (LCPT; LCP-tacrolimus; Envarsus XR) or receiving standard-of-care capsule tacrolimus (PR-Tac; Prolonged-release tacrolimus; Advagraf/IR-Tac; immediate-release tacrolimus; Prograf). Methods: A systematic review was conducted for all randomized controlled trials (RCTs) and cohort studies investigating the outcomes in KTRs receiving LCPT or PR-Tac/IR-Tac. We systematically searched PubMed, Web of Science, and EMBASE, with no language restriction. The registered trials and references listed in relevant studies were also searched. Data were extracted for pharmacokinetic (PK) profile, tacrolimus trough level (TTL), changes in estimated glomerular filtration rate (eGFR) and serum creatinine (Scr), biopsy-proven acute rejection (BPAR) rate, delayed graft function (DGF) rate, post-transplant diabetes mellitus (PTDM) rate, tremor rate (TR), death rate (DR), and rate of infection by cytomegalovirus (CMV). This study was registered with PROSPERO (registration number: CRD42023403787). Results: A total of seven eligible articles including 1,428 patients with 712 in the LCPT group versus 716 in the PR-Tac/IR-Tac group were included in this study for evidence synthesis. The baseline characteristics of the LCPT group, the PR-Tac group and the IR-Tac group were similar. The pooled analysis showed higher PK in the LCPT group, and this result was consistent with those of all the included studies. In addition, no significant difference was observed for other outcomes. Conclusions: Considering heterogeneity between studies and potential bias, care providers should select agents based on patient-specific factors and their clinical experience for the immunosuppressive treatment of de novo KTRs.